Buckling analysis of cracked columns by XFEM - Mohammad Reza Shirazizadeh; Hossein Shahverdi; Ali Imam (International Journal of Advanced Design and Manufacturing Technology, 2016)
This paper focuses on using the recently developed extended finite element model for buckling analysis of edge cracked columns under concentric axial load. The effect of crack depth and its location on the carrying capacity of columns is studied. The effect of different boundary conditions is also investigated. Numerical examples are offered to show the efficiency and effectiveness of the proposed method. The presented results are compared with analytical and experimental works available in the literature. Good agreement with experiment is shown, although the difference with analytical results is considerable for columns with deeper cracks. The reason of this difference is discussed.  It is shown that the proposed method is more accurate than the analytical methods which are developed based on rotational spring models.